THE COMPLETE CLINICAL RESPONSE IN RECTAL CARCINOMA AFTER CHEMO RADIATION: Rectal Carcinoma After Chemo Radiation - Manzoor, Ammara; Haider, Ghulam; Zahoor, Saima; Bai, Ravisha; Khan, Muhammad Ejaz; Ahmad, Maqbool (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the complete clinical response in rectal carcinoma after neoadjuvant chemo radiation. Study Design: Cross-sectional study. Place and Duration of Study: This study was conducted in Clinical Oncology department, Jinnah Postgraduate Medical Centre Karachi, from Jan 2016 to Jan 2017. Material and Methods: Seventy Two Patients meeting the inclusion criteria were enrolled in study after complete staging workup. Neoadjuvant concurrent chemoradiotherapy was planned, consisting of oral capecitabine 825mg/m2 BID five days a week along with 50.4 Gy Radiotherapy with linac machine. Radiation was delivered over a period of 5 weeks at a rate of 1.8 Gy/day. Patients received Radiotherapy in Atomic Energy Medical Centre (AEMC) and in Sindh Institute Urology & Transplant (SIUT), Radiation department. Chemotherapy was given in clinical oncology department of JPMC. Sixty one patients completed planned treatment and were available for post concomitant chemo radiotherapy response assessment with Pelvic CT/MRI after 6-8 weeks of completion of concomitant chemo radiotherapy. Response assessment was done according to Response Evaluation Criteria in solid tumor (RECIST) criteria version 1.1 and then Patients were referred for surgical evaluation. Result: A total of 61 cases of locally advanced adenocarcinoma rectal cancer patients were included in the study. Mean age of the patients was 41 years with ± 17.06 years SD. Complete clinical response was identified in 4 (6.6%) while 31 (50.8%) were identified as partial response, progressive disease was 13 (21.3%) and 13 (21.3%) were with stable disease. All confounding variables were found statistically significant with p-value found less than 0.05. Conclusion: Neo-adjuvant chemoradiotherapy for locally advanced rectal cancer is associated with high rates of tumor response in terms of downs tagging (complete & partial) and is relatively safe with acceptable morbidity, which favors its use in future.